Analysis of Public Communication Strategy in Teluk Bintuni Regency in the Digital Era - Lestari, Mugi; Surya P, Dhika (Communication In Research And Publications, 2024)
This study explores the digital-based public communication strategies implemented by the Teluk Bintuni Regency Government, with a focus on the challenges and opportunities of utilizing technology to convey information to the public. As a developing region in West Papua, Teluk Bintuni faces unique geographical and infrastructural challenges, alongside a diverse cultural landscape. The study highlights how digital media, including social media platforms, websites, and online applications, is used to disseminate government policies, development programs, and emergency information. However, it also identifies key barriers such as limited internet access in rural areas, low digital literacy, and insufficient technological infrastructure. The study examines how traditional communication methods, such as local language usage and the involvement of community leaders, play a vital role in ensuring effective communication in remote areas. Additionally, the research provides strategic recommendations for overcoming these challenges, such as improving digital infrastructure, enhancing digital literacy, and fostering collaboration with various stakeholders. The findings underscore the need for a hybrid communication approach that integrates both digital and traditional methods to bridge the digital divide and ensure inclusive public communication in Teluk Bintuni.